School Finance & the Distribution of Equal Educational Opportunity in the Postrecession U.S. (December 2016) - Baker, Bruce D.
Abstract : This article builds on the national school funding fairness report annually produced by the Education Law Center (ELC) of New Jersey. This article expands prior analyses in two directions. First, while ELC analyses evaluate only the most recent 3 years of data, we track school funding progressiveness (the relative targeting of funding to districts serving economically disadvantaged children) for all states from 1993 to 2012. Second, this article explores in greater depth the consequences of school funding levels, distributions and changes for specific classroom resources provided in schools. The analyses presented herein validate that variations in available revenues and expenditures are associated with variations in children's access to real resources—as measured by the competitiveness of the wages paid to their teachers and by pupil‐to‐teacher ratios and class sizes.